Creating and sustaining a high-performing tennis culture - Nash, C.; Crespo, M.; Martínez-Gallego, R. (International Sport Coaching Journal, 2025)
The coach is identified as a key actor in the development of a high-performing culture in sport, in this case, tennis. Using mixed-methods research design, we investigated the views of the participating high-performance tennis coaches on the International Tennis Federation/Olympic Solidarity coach education and certification programme conducted in Spain, and how they felt their involvement made an impact within their national organisations, by enabling them to develop and implement a coach-created high-performing environment. We collected data using both interview and survey procedures. Our findings from the survey indicated that the participating coaches found the programme to be very helpful to their practice, especially to their long-term tennis development, the structure and organisation of effective tennis programmes, and the implementation of appropriate training methods for their players. Content analysis of the interviews revealed three main themes related to creating a high-performing tennis culture: (a) high-performing environment, (b) deliberate focus on growth and development, and (c) obstacles to creating a tennis culture. We discuss the challenges associated with transferring a successful sports development programme to a different cultural environment and conclude with some key points for effective implementation.